MICE - Prospect direction of Vietnam tourism - Phạm, Hải Yến (2020)
Although it has been introduced in Vietnam since the 1990s, MICE tourism has shown huge potential compared to other makers: MICE visitors often come in large groups, have long stays and are big spenders. With the increase of tourism resources, people-friendly Vietnam has begun to focus on the MICE market in recent years. However, in the development process, there are many difficulties and inadequacies. In this article, the author will focus on analyzing the advantages and disadvantages of MICE tourism in Vietnam and offer some solutions to this potential market development.